Increasing the throughput of label-free cell assays to study the activation of G-protein-coupled receptors by using a serial agonist exposure protocol - Stolwijk, J. A.; Skiba, M.; Kade, C.; Bernhardt, G.; Buschauer, A.; Hübner, Harald; Gmeiner, Peter; Wegener, J. (Integrative Biology, 2019)
Label-free, holistic assays, monitoring, for example, the impedance of cells on electrodes, are gaining increasing popularity in the evaluation of G-protein-coupled receptor (GPCR) ligands. It is the strength of these approaches to provide the integrated cellular response non-invasively, highly automated and with a device-dependent time resolution down to several milliseconds. With an increasing number of samples to be studied in parallel, the available time resolution is, however, reduced and the cost for the disposable sensor arrays may become limiting. Inspired by protocols from organ pharmacology, we investigated a simple serial agonist addition assay that circumvents these limitations in impedance-based cellular assays. Using a serial addition of increasing concentrations of a GPCR agonist while continuously monitoring the sample's impedance, we were able to establish a full concentration-response curve for the endogenous agonist histamine on a single layer of U-373 MG cells endogenously expressing the histamine 1 receptor (H1R). This approach is validated with respect to conventional, parallel agonist addition protocols and studies using H1R antagonists such as mepyramine. Applicability of the serial agonist addition assay was shown for other GPCRs known for their signaling via one of the canonical G-protein pathways, G(q), G(i/0) or G(s) as well. The serial agonist addition protocol has the potential to further strengthen the output of label-free analysis of GPCR activation.